Study of hardness and microstructure of Fe-C-Si-Mn-B hardfacing alloy - P M, Aaqib Rashad; Hrairi, Meftah; M, Santhosham; Boopathy, Rajendra (2013)
Iron based alloys are normally utilized for abrasive coatings to resist wear. Chromium added iron alloys are commonly chosen for hardfacing, which is one of the surface improvement methods. Such alloys are costly and give a moderate hardness to the deposits, due to the large addition of chromium. Fe-C-Si-Mn alloys show hardness up to 450VHN, without heat treatment, which is an established fact. In this work boron is added to Fe-C-Si-Mn welding alloys, deposits are made on low carbon steel substrates and resultant hardness is found to be an average of 650VHN, which is equivalent to some of the chromium containing ferrous alloys. Boron addition to Fe-C-Si-Mn alloy causes it to harden further, such that it can be utilized to combat wear. A few alloys are produced with the addition of boron (< 0.02Wt %) and tested for hardness and microstructure. Fe-C-Si-Mn-B alloys produced in the form welding electrodes can be utilized for hardfacing purposes with specific industrial applications. Micrographs reveal the presence of lower bainite and tempered martensite.